2019
DOI: 10.14202/vetworld.2019.1975-1986
|View full text |Cite
|
Sign up to set email alerts
|

Molecular survey and interaction of common respiratory pathogens in chicken flocks (field perspective)

Abstract: Aim:The present study was designed for the detection of the most prevalent respiratory infections in chicken flocks and clarifying their interaction and impact on flock health. Materials and Methods:A total of 359 serum samples were collected from 55 backyard chickens and tested using commercial enzyme-linked immunosorbent assay kits to determine the seroprevalence of Newcastle disease virus (NDV), infectious bronchitis virus (IBV), influenza type A, Mycoplasma gallisepticum (MG), and Mycoplasma synoviae (MS).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Infected chicken flocks usually experience mild respiratory distress, diarrhoea, decreased body weight in broilers, and a drop in egg production in layer hen flocks, the mortality rates are generally low, below 20% [ 10 – 14 ]. However, infected poultry are more susceptible to secondary infections, including bacterial infection and in such cases the mortality rate can increase up to 65% [ 15 18 ]. It has been shown that certain bacteria, such as Staphylococcus spp.…”
Section: Introductionmentioning
confidence: 99%
“…Infected chicken flocks usually experience mild respiratory distress, diarrhoea, decreased body weight in broilers, and a drop in egg production in layer hen flocks, the mortality rates are generally low, below 20% [ 10 – 14 ]. However, infected poultry are more susceptible to secondary infections, including bacterial infection and in such cases the mortality rate can increase up to 65% [ 15 18 ]. It has been shown that certain bacteria, such as Staphylococcus spp.…”
Section: Introductionmentioning
confidence: 99%
“…However, instead of manifesting as a single infection, MG often presents as one of several pathogens in a complex of multifactorial diseases. The synergistic interactions among these respiratory pathogens can result in severe clinical symptoms, a high incidence, and increased mortality rates (Naylor et al, 1992;Sid et al, 2015;Abdelaziz et al, 2019).…”
Section: Clinical Featuresmentioning
confidence: 99%
“…It affects all poultry species in all types of production systems ( 80 ) and all chicken age groups ( 81 ). Furthermore, APEC result in localized and systemic infections in poultry, resulting in production loss and rapid mortality ( 82 , 83 ).…”
Section: Negative Influence Of Bacteria On Host Healthmentioning
confidence: 99%